Entire Flow Field Modeling Including Wake Region through Improved Finite-State Method - Huang, Jian-Zhe; Peters, David (Journal of Vibration Testing and System Dynamics, 2026)
In the recent decades, the accuracy and robust of finite state inflow model to provide the velocity on the disk have been greatly improved. It is adequate to compute the thrust, pitch and roll moment real time for normal flight conditions. For lifting rotor flying close to a non-penetrable surface, the wake will interact with the inflow of the lifting rotor. Additionally, for co-axial rotors the wake of the upper rotor influences the lower rotor. Therefore, it is necessary to develop a model to compute the flow field in the wake since the Peters-He model cannot give the induced velocity below the rotor disk. In this paper, the improved finite state model will be introduced to compute the axial induced velocity everywhere in the flow field including wake and downstreamregions. The adjoint theorem will be introduced, and the computational efficiency of the convolution method and numerical algorithm for computing the adjoint varibales with time delay will be compared. With the parameters of a Harrington rotor, the results in the time domain for such a rotor in hover and forward flight conditions will also be illustrated.